Pengaruh Kemampuan Manajerial Terhadap Keberhasilan Usaha - Andhika Agung Pamungkas; Maya Setiawardani (Jurnal Riset Bisnis dan Investasi, 2015)
The business world is much in demand by many people in the world and especially in Indonesia, evidenced by many new businesses that have sprung up, be it micro, small, and medium enterprises (SMEs) and large businesses. Competition and the development of the business world are getting stronger and sharper, so to improve the handling of a serious effort is required of every entrepreneur to be able to compete with other companies. Where one of the efforts to increase business success is by increasing the internal and external resources. Including that competition and business development that occurs in the center of the shoe industry Cibaduyut Bandung. This study aims to determine how the influence of managerial capability as one of the internal resources to business success entrepreneurs shoes in the shoe industry center Cibaduyut Bandung. The population in this study consisted of 128 shoe entrepreneurs which produce their product by themselves. In this study, the independent variable is the managerial ability and the dependent variable is the success of the business. Data collected through questionnaires for primary data and documentation for secondary data. Data were analyzed using simple linear regression technique with SPSS 22.00 program for Windows. Results of the study provide findings that the managerial capabilities have positive and significant effect on business success.